The Economics of Teacher Supply in Indonesia - Chen, Dandan (2012)
This paper examines the phenomenon of the over-supply of teachers but shortage of qualified teachers in Indonesia. Using a theoretical framework of government-dominated market with government-set wage rate and demand for teachers, the analysis explores how teacher supply, particularly the composition of the teaching force with low or high qualification, would be determined by current and future public policies. Using 2001 to 2008 Indonesian Labor Force Survey data, the paper further estimates the potential effect of the most recent teacher law, which could give college educated teachers a significant pay increase, on the composition of the Indonesian teaching force with differentiated education backgrounds. Using a sample of workers with college education, the author finds that the relative wage rate of teachers and that of alternative occupations significantly influence the decision of college educated workers to become teachers. It is also found that the wage rate set by the most recent teacher law would increase the share of teachers approximately from 16 to 30 percent of the college-educated labor force. This increase that is due to the new government-set wage rate, would result in a pupil-teacher ratio of 24 to 25 pupils per teacher with college education, but will require a more than 31 percent increase in the wage bill for teacher salaries. The empirical approach of this paper is derived from a structural model that takes into account the endogeneity of the wage rate and corrects for sample-selection bias due to occupational choice.